Mechanisms of Scarring in Focal Segmental Glomerulosclerosis. (September 2019) - Zhong, Jianyong; Whitman, Jacob B.; Yang, Hai-Chun; Fogo, Agnes B.
Focal segmental glomerulosclerosis (FSGS) presents with scar in parts of some glomeruli and often progresses to global and diffuse glomerulosclerosis. Podocyte injury is the initial target in primary FSGS, induced by a circulating factor. Several gene variants, for example, APOL1, are associated with increased susceptibility to FSGS. Primary FSGS may be due to genetic mutation in key podocyte genes. Increased work stress after loss of nephrons, epigenetic mechanisms, and various profibrotic pathways can contribute to progressive sclerosis, regardless of the initial injury. The progression of FSGS lesions also involves crosstalk between podocytes and other kidney cells, such as parietal epithelial cells, glomerular endothelial cells, and even tubular epithelial cells. New insights related to these mechanisms could potentially lead to new therapeutic strategies to prevent progression of FSGS.